A Studying of The Qur'an Annisa' Verse 3 Regarding The Phenomenon Of Paid Polygamy Mentoring: STUDYING OF THE QUR'AN ANNISA' VERSE 3 REGARDING THE PHENOMENON OF PAID POLYGAMY MENTORING Irma Nur Hayati, Fauzan Zenrif Student in The Islamic University of Malik Maulana Ibrahim Malang, Malang Indoneisa1 Lecture in The Islamic University of Malik Maulana Ibrahim Malang, Indonesia Lecture in The Islamic University of Malik Maulana Ibrahim Malang, Indonesia - Irma Nur Hayati Hayati; Fauzan Zenrif Zenrif (Fakultas Syariah Program studi Hukum Keluarga Islam IAI Al- Qodiri, 2022)
Abstract: This paper tries to reveal another side of the phenomenon of violence against women which is currently viral on social media. It is related to the case of paid polygamy mentoring which is not in accordance with Islamic law and the conditions of Indonesian society in particular. The glorification of women's violence is a frightening threat to marriages that can start with polygamy. In the sense of violence, Polygamy has implication for the concept of gender, both in terms of gender, physical, sexuality, and psychological differences.In fact, the scholars explained in the Qur'an, namely,